The Self-Leadership Profile of High School Students and Its Implications for Personal-Social Guidance and Counseling - Zulhakim, Aji; Rochani, Rochani; Khairun, Deasy Yunika (Indonesian Journal of Guidance and Counseling Studies, 2025)
Background: This study was motivated by the importance of developing self-leadership in students, which in turn influences their motivation, self-management, and responsibility in daily life. Self-leadership plays a crucial role in shaping students' character and influencing their academic and social success. Objective: This study aims to provide an overview of students' self-leadership and to design a personalized social guidance and counseling program to enhance students' self-leadership. Method: This study employed a quantitative descriptive research design with a random sampling technique, involving 106 second-year students at SMAN 1 Jawilan. This study used indicators of behavioral focus, natural reward strategies, and constructive thinking to measure students' self-leadership. Results: The results showed that 65% of students fell into the moderate self-leadership category, 19% into the high category, and 16% into the low category. Conclusion: Based on these results, it is essential to design a guidance program that enhances students' ability to lead themselves, manage their goals, and foster a greater sense of responsibility. Contribution: This study contributes to the development of a guidance program that can strengthen students' self-leadership, aiming to improve self-management and awareness of self-potential within the school environment.